Regulatory Transformation of House of Worship Construction to Realize Substantive Justice for Minority Groups - Thohir (JURNAL ILMIAH GEMA PERENCANA, 2026)
The urgency of this policy analysis centers on the systematic barriers faced by minority groups in Frontier, Outermost, and Least Developed (3T) regions regarding the establishment of houses of worship, resulting from the rigid regulations of the Joint Ministerial Decree Numbers 9 and 8 of 2006. Administrative requirements mandating 90 users and 60 local supporters have become impossible thresholds to meet in sparsely populated areas, thereby triggering substantive injustice and structured licensing discrimination. This analysis employs a descriptive qualitative methodology through policy document studies and observations of regulatory implementation at the street-level bureaucracy, assessing policy alternatives using William N. Dunn’s evaluation criteria. The results and discussion indicate that the paradigm of administrative centralism has neglected the micro-demographic context of marginal regions, leading to the emergence of a "majority veto" within the permit recommendation process. It was found that rigid policy standardization without asymmetric discretion has undermined the constitutional right to worship for minority adherents in remote areas. As a strategic solution, a regulatory transformation is recommended through the rationalization of quantitative thresholds to 40 users and 30 supporters specifically for 3T regions, supported by the digitalization of integrated monitoring systems and the strengthening of religious counselors' roles as certified conflict mediators to ensure inclusive and adaptive legal certainty.